(untitled) - Bud, Robert (Cambridge,New York, NY, 1993)
This book shows, for the first time, how modern biotechnology grew out of this century's hopes for a new relationship between biology and engineering. Long before recombinant DNA, these promised a new kind of technology. By exploring the rich and surprisingly overlooked complex of prophesies, industrial and scientific development and government programs, the book sheds new light on the expectations now held for biotechnology. A world-wide view, covering developments, not just in America but also in Europe and Japan, uncovers surprising links. This makes possible a coherent story to supersede the historical notes which have been available until now. This first history of biotechnology provides a readable and challenging account that will appeal to anyone interested in the development of this key component of modern industry.
Keywords: Biotechnology,Công nghệ sinh học; History,Lịch sử